(untitled) (International Journal of Food and Nutritional Sciences, 2022)
All trusts and societies registered in the state of Gujarat are considered as a trust as per Gujarat Public Trust Act-1950. All voluntary organizations registered under Gujarat Public Trust Act-1950 must contribute to the public trust administration fund as define in section-57 and section-58 of the Gujarat Public Trust Act-1950. As per the proportion of gross annual income of the trust the contribution is calculated and direction for calculating the contribution is given in rule 32 of The Bombay Public Trust (Gujarat) Rules, 1961. Before the existence of Gujarat State, it was governed by Bombay Public Trust Act-1950. Voluntary organization working for health, education and animal veterinary activity are exempted from paying contribution to the public trust administration fund and other organizations must contribute 2% of their income. In this study section-57 and section-58 of the Gujarat Public Trust Act and Rule 32 of The Bombay Public Trust (Gujarat) Rules, 1961 is critically analyzed.